(untitled) (Revista Electrónica REDINE, 2018)
This investigation of Field had for objective to Execute a methodology of Learning that optimizes the Academic Yield in the students of the first semester of the Program Agroindustrial Engineering of the UCLA. It was of Experimental type with a Design Cuasiexperimental. He/she was carried out a diagnosis previously to establish the first floor yield using an instrument based on the university project “the student’s of the Venezuelan Universities National Profile.” In the Experimental phase the population was conformed by the 58 students of the first semester of the cohort I-2011 that were divided in two groups; the experimental one and the control. The Methodology of Based Learning was used in Problems like method to optimize the Yield. The instrument went the definitive notes when concluding the semester. The results were obtained through a Test “t” of Student where the values of each one of the classes went superior to that of the chart in a level of 0.05 with 56 gl. You concluded that the Methodology of Based Learning in Problems contributes to optimize the student Academic Yield to be an innovative method.